Recruitment of NAADP-sensitive acidic Ca2+ stores by glutamate. - Pandey, V; Chuang, C; Lewis, A; Aley, P; Brailoiu, E; Dun, N; Churchill, G; Patel, S (2009)
NAADP (nicotinic acid-adenine dinucleotide phosphate) is an unusual second messenger thought to mobilize acidic Ca(2+) stores, such as lysosomes or lysosome-like organelles, that are functionally coupled to the ER (endoplasmic reticulum). Although NAADP-sensitive Ca(2+) stores have been described in neurons, the physiological cues that recruit them are not known. Here we show that in both hippocampal neurons and glia, extracellular application of glutamate, in the absence of external Ca(2+), evoked cytosolic Ca(2+) signals that were inhibited by preventing organelle acidification or following osmotic bursting of lysosomes. The sensitivity of both cell types to glutamate correlated well with lysosomal Ca(2+) content. However, interfering with acidic compartments was largely without effect on the Ca(2+) content of the ER or Ca(2+) signals in response to ATP. Glutamate but not ATP elevated cellular NAADP levels. Our results provide evidence for the agonist-specific recruitment of NAADP-sensitive Ca(2+) stores by glutamate. This links the actions of NAADP to a major neurotransmitter in the brain.